A Qualitative Study of Traditional Bone Setters in South India: A Case Series - Isaacs-Pullins, Sharon; Vaz, Manjulika; Murthy, Hariram; Hughes, Dorothy; Kallail, K. James (Kansas Journal of Medicine, 2022)
INTRODUCTION. There are approximately 70,000 Traditional Bone Setters (TBS) in India, who have no formal education or training in modern medicine but treat approximately 60% of bone related trauma. This study investigated the history of TBS, why they are so popular, and their methods.METHODS. From a list of TBS from four states in South India, a purposive and convenience sampling method identified participants. One lead TBS from each state was interviewed. With recommendations from these TBS, a total of six participants were interviewed on Zoom® in their native dialect and these interviews were transcribed into English. The data were analyzed using a constant comparative method which included several iterations to refine common themes and determine counterfactual and specific focal points from each interview.RESULTS. Six overarching themes emerged: (1) history of traditional bone setters, (2) occupations outside bone setting, (3) training, certification, education, accolades, (4) patient characteristics and success stories, (5) infrastructure and approach to diagnosis/treatment, and (6) limitations of practice, challenges, and social relevance. The history of traditional bone setting is thousands of years old and passed down within families generationally.CONCLUSIONS. In rural India, where a large part of the population lives in poverty and without access to modern medicine, traditional healers provide a much-needed service, often without charge, and consequently, the income is not sufficient without other occupations such as farming. They follow a similar approach to diagnosis and treatment of simple fractures and dislocations as modern medical practitioners. Most would like to share their knowledge and collaborate with ayurvedic and allopathic practitioners and simply want to be respected and supported.